Low-carbon and environment-friendly centrifugal electric pole concrete and preparation process thereof
Patent Information
- Application Number
- CN202611374790.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种低碳环保的离心电杆混凝土及其制备工艺,解决了现有技术存在余浆分流易受检测值波动影响、回用物料与水分计量不准确、部分碳化终点判定依据不足以及离心脱水与固体排出缺少联合控制的问题
1、本发明采用连续检测值的移动平均值对离心余浆进行分流,并对高固体含量余浆和低固体含量余浆分别处理;两类回用物料按照余浆烘干固体质量计量,同时扣除其带入的水分,可减少余浆固体质量分数波动对粉体材料和总水用量的影响。
Smart Images

Figure CN122897643A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete materials technology, specifically to a low-carbon and environmentally friendly centrifugal pole concrete and its preparation process. Background Technology
[0002] Centrifugal concrete poles are typically made from silicate cement, mineral admixtures, aggregates, water, and additives, and then molded, centrifuged, and cured to form the poles. To reduce the amount of silicate cement used, existing mix proportions can incorporate granulated blast furnace slag powder, coal gangue powder, and other industrial solid wastes. The residual slurry discharged during the centrifugation process contains water, cement particles, mineral admixture particles, and hydration products, making it reusable.
[0003] The solids content of centrifuged slurry varies with production batches and discharge stages. When diverting slurry based on single test results or reusing it directly according to wet material quality, it is difficult to separately measure the solids and water content in the slurry, which will change the amount of powder materials and total water content in subsequent concrete. Using the same treatment method for slurry with different solids content also fails to differentiate between their solids content and liquid phase ratio.
[0004] Low-solids slurry contains alkaline components. When reused directly without treatment, its alkalinity and moisture content fluctuate. When carbonization is performed, it is difficult to determine the endpoint solely based on pH value, as this makes it challenging to simultaneously ascertain the degree of carbon dioxide absorption and alkalinity retention. Excessive carbonization can also reduce the titratable alkalinity of the slurry, affecting subsequent reaction conditions of the mineral admixtures.
[0005] Existing centrifugal molding processes typically operate according to preset centrifugal acceleration and time, or determine the stopping time based on the discharge volume. This method does not separately calculate the discharged water volume and the mass of discharged solids, making it difficult to simultaneously determine the degree of concrete dehydration, the amount of powder material discharged, and the discharge status. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a low-carbon and environmentally friendly centrifugal pole concrete and its preparation process, solving the problems of existing technologies such as the slurry diversion being easily affected by fluctuations in detection values, inaccurate measurement of recycled materials and moisture, insufficient basis for determining some carbonization endpoints, and lack of joint control between centrifugal dehydration and solid discharge.
[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a low-carbon and environmentally friendly centrifugal pole concrete, made from raw materials comprising the following parts by weight: Based on 100 parts by weight of powder materials, the composition includes: 53-58 parts of silicate cement, 24-26.8 parts of granulated blast furnace slag powder, 10-10.5 parts of calcined coal gangue powder, 3-6 parts of high-solids content residual slurry, 2-5 parts of partially carbonized residual slurry composite slurry, 0.2-1.5 parts of desulfurized gypsum, 125-145 parts of fine aggregate, 250-290 parts of coarse aggregate, 25-29 parts of total water, 0.18-0.30 parts of polycarboxylate superplasticizer solids, and 0.01-0.03 parts of active ingredient of organosilicon defoamer.
[0008] The amount of high-solids content residual slurry used is calculated based on the dried solids of the high-solids content residual slurry, and the amount of partially carbonized residual slurry composite slurry used is calculated based on the dried solids of the partially carbonized residual slurry.
[0009] By adopting the above technical solution, the dry solids from high-solids-content slurry and the dry solids from partially carbonized slurry are included in the powder material based on dry weight, while the moisture introduced by the slurry and additives is included in the total water. This metering method allows the wet material dosage of the two types of slurry to be converted based on the measured solids mass fraction, reducing the impact of changes in the solids mass fraction of the slurry on the amount of powder material used and the total water content.
[0010] Granulated blast furnace slag powder, calcined coal gangue powder, two types of residual slurry dried solids, and desulfurized gypsum jointly replace part of the silicate cement. Cement particles and mineral admixture particles in the high-solids residual slurry are reintroduced into concrete mixes within the allowable reuse period, and the not-fully-hydrated cementitious materials can continue to participate in hydration. The low-solids residual slurry, after partial carbonization and concentration, is added in the form of a partially carbonized residual slurry composite slurry, enabling the reuse of the low-solids residual slurry and the absorption of some carbon dioxide.
[0011] Preferably, based on 100 parts by weight of powder materials, the composition includes 55 parts silicate cement, 25 parts granulated blast furnace slag powder, 10 parts calcined coal gangue powder, 5 parts high-solids content residual slurry, 4 parts partially carbonized residual slurry composite slurry, 1 part desulfurized gypsum, 135 parts fine aggregate, 270 parts coarse aggregate, 27 parts total water, 0.24 parts polycarboxylate superplasticizer solids, and 0.02 parts effective component of organosilicon defoamer. The amount of high-solids content residual slurry used is based on the dried solids of the high-solids content residual slurry, and the amount of partially carbonized residual slurry composite slurry used is based on the dried solids of the partially carbonized residual slurry.
[0012] The above proportions specify the mass ratio of the two types of residual slurry drying solids in the powder material, and limit the dosage of aggregate, total water, polycarboxylate superplasticizer, and silicone defoamer. The polycarboxylate superplasticizer is used to adjust the fluidity of the concrete, while the silicone defoamer is used to reduce residual slurry and air bubbles introduced during the mixing process.
[0013] Preferably, the high-solids content slurry is obtained by continuously monitoring the solids mass fraction of the centrifuged slurry and diverting it based on the moving average of the continuous monitoring values, ensuring the high-solids content slurry is within the allowable reuse time. The partially carbonized slurry composite slurry is prepared by mixing low-solids content slurry with calcined coal gangue powder and desulfurized gypsum after partial carbonization and concentration. During partial carbonization, the net carbon dioxide absorption is measured and the current titratable alkalinity is determined; the partial carbonization endpoint is determined based on both the net carbon dioxide absorption and the current titratable alkalinity.
[0014] By adopting the above technical solution, the moving average of continuous test values is used to characterize the solid mass fraction of centrifuged slurry over a period of time, reducing the impact of fluctuations in single test values on the grading results. High-solids-content slurry is not carbonized and is used in concrete batching within the allowable reuse period. Low-solids-content slurry undergoes partial carbonization, allowing the two types of slurry to be treated separately according to their respective solid content and subsequent uses.
[0015] Net carbon dioxide absorption represents the difference between the cumulative amount of carbon dioxide entering the carbonization system and the cumulative amount of carbon dioxide exiting the carbonization system. Current titratable alkalinity represents the amount of acid consumed per unit of residual slurry during the carbonization process. Net carbon dioxide absorption is used to define the degree of carbonization that has occurred, while current titratable alkalinity is used to define the remaining alkaline components. Both parameters are used together to determine the partial carbonization endpoint, distinguishing between uncarbonized, partially carbonized, and near-completely carbonized processing states.
[0016] Preferably, the calcined coal gangue powder is obtained by calcining kaolinite-containing coal gangue raw materials at 650–800℃ for 30–120 min and then grinding them. The solid content of the partially carbonized residual slurry is 1 part by weight, the calcined coal gangue powder in the partially carbonized residual slurry composite slurry is 0.5–1.5 parts by weight, the desulfurized gypsum is 0.1–0.3 parts by weight, and the solid content of the partially carbonized residual slurry composite slurry is 50%–65%.
[0017] During calcination, kaolinite-containing coal gangue raw materials undergo a dehydroxylation reaction. The structural water in the kaolinite is removed by heat and discharged as steam, transforming the hydrated aluminosilicate component into a dehydroxylated, active silica-alumina component. This active silica-alumina component gradually dissolves in the alkaline liquid phase formed during cement hydration and reacts with the calcium-containing components in the system to form calcium-containing silicate hydration products and aluminosilicate hydration products. The composition of these hydration products is affected by the calcium-to-silicon ratio, aluminum content, and curing conditions, and is not expressed using fixed stoichiometric ratios.
[0018] The active silica-alumina components formed after calcination gradually dissolve in the alkaline liquid phase formed during cement hydration and react with the calcium-containing components in the system to form calcium-containing silicate hydration products and aluminum-containing silicate hydration products. This process is not expressed using a fixed stoichiometric ratio because the actual product composition varies with the calcium-silicon ratio, aluminum content, and curing conditions.
[0019] During the partial carbonization of the low-solids slurry, the introduced carbon dioxide enters the aqueous phase of the slurry and consumes some hydroxide ions, forming carbonate ions and water. The formed carbonate ions combine with calcium ions in the slurry to form calcium carbonate; carbon dioxide can also react with calcium hydroxide in the slurry to form calcium carbonate and water. The partial carbonization treatment is stopped before all the alkaline components in the low-solids slurry are consumed, so that the resulting partially carbonized slurry retains a certain titratable alkalinity.
[0020] The concentrated carbonization residue is premixed with calcined coal gangue powder and desulfurized gypsum, allowing the calcined coal gangue powder to contact the alkaline liquid phase and calcium-containing components in the residue. The desulfurized gypsum provides sulfate ions, which can participate in the formation of ettringite-like hydration products with aluminum-containing components in the cementing system.
[0021] Therefore, the high-solids-content waste slurry is used to reuse the solid cementitious materials within it, while the low-solids-content waste slurry undergoes partial carbonization to adjust the carbon dioxide absorption and alkalinity retention levels, and is then combined with calcined coal gangue powder and desulfurized gypsum to form a partially carbonized waste slurry composite slurry. After separate treatment, the two types of waste slurry are incorporated into the concrete mix design based on the mass of the dried solids, enabling the utilization of industrial solid waste, waste slurry reuse, and total water control to be implemented within the same mix proportion.
[0022] Secondly, the present invention provides a low-carbon and environmentally friendly process for preparing centrifugal pole concrete, comprising the following steps: The solids mass fraction of the centrifuged slurry is continuously monitored, and the slurry is split based on the moving average of the continuous monitoring values. When the moving average is not less than a preset high solids content threshold, the centrifuged slurry is split into high solids content slurry; when the moving average is not greater than a preset low solids content threshold, the centrifuged slurry is split into low solids content slurry; when the moving average is between the two thresholds, the centrifuged slurry is split into intermediate solids content slurry.
[0023] The high-solids content slurry is kept on standby within the allowable reuse period. The low-solids content slurry is partially carbonized and concentrated, and then mixed with calcined coal gangue powder and desulfurized gypsum to obtain a partially carbonized slurry composite slurry.
[0024] Based on the mass of dried solids from the high-solids content residual slurry and the mass of dried solids from the partially carbonized residual slurry in the concrete mix, and combined with the measured solids mass fraction, the wet addition amount of the high-solids content residual slurry and the addition amount of the partially carbonized residual slurry composite slurry are determined. The additional mixing water is obtained by subtracting the water contained in the high-solids content residual slurry, the partially carbonized residual slurry composite slurry, the polycarboxylate superplasticizer, and the silicone defoamer from the total water volume.
[0025] The high-solids-content residual slurry, partially carbonized residual slurry composite slurry, and additional mixing water are mixed with the remaining concrete raw materials to obtain centrifugal pole concrete.
[0026] By adopting the above technical solution, the centrifugal slurry is diverted according to the moving average of continuous detection values. The high-solids-content slurry and the low-solids-content slurry enter the direct reuse and partial carbonization treatment paths, respectively. The two types of reused materials are measured according to the mass of solids in the dried slurry, and the moisture they carry is deducted from the total water volume, so that the powder materials and moisture adopt a unified batching standard.
[0027] Preferably, the detection cycle for solid content is 1–5 seconds, and the moving average is calculated using 5–15 consecutive detection values. The preset high solid content threshold is 30%, and the preset low solid content threshold is 25%. If the preset number of consecutive detection values is not reached, the centrifuged slurry is diverted into slurry with intermediate solid content, and the intermediate solid content slurry is homogenized and re-detected. The allowable reuse time for high solid content slurry is the shorter of 30 minutes from its generation and one-third of the measured initial setting time of the corresponding concrete.
[0028] By adopting the above technical solution, the moving average value is used to reduce the impact of changes in the single solids mass fraction test value on the diversion result. When the number of test values is insufficient, the slurry will not directly enter the high-solids content or low-solids content slurry treatment path; the allowable reuse time is used to limit the reuse time of high-solids content slurry.
[0029] Preferably, the low-solids slurry is divided into a reference material and a material for partial carbonization. Carbon dioxide gas is introduced into the reference material. When the net carbon dioxide absorption corresponding to the increase in unit dry solids of the slurry for 30 minutes is no greater than 1% of the previously accumulated net carbon dioxide absorption, and the pH value is maintained between 8.5 and 9.5, the cumulative net carbon dioxide absorption corresponding to the unit dry solids of the slurry is determined as the reference value for fully carbonized carbon dioxide absorption.
[0030] The ratio of net carbon dioxide absorption corresponding to the unit residual slurry drying solids to the baseline value of carbon dioxide absorption after complete carbonization, and the ratio of the current titratable alkalinity to the titratable alkalinity before carbonization, shall be taken from one of the following three ranges: The net carbon dioxide absorption rate is 30%–35%, and the titratable alkalinity retention rate is 55%–60%. The net carbon dioxide absorption rate is 38%–42%, and the titratable alkalinity retention rate is 48%–52%. The net carbon dioxide absorption rate is 45%–50%, and the titratable alkalinity retention rate is 40%–45%.
[0031] The net carbon dioxide absorption ratio indicates the degree of carbonization relative to the baseline value for fully carbonized carbon dioxide absorption, while the titratable alkalinity retention ratio indicates the alkaline components retained after partial carbonization. Gas flow is stopped when both parameters simultaneously reach their corresponding ranges, avoiding the need to determine the partial carbonization endpoint solely based on pH.
[0032] Preferably, a portion of the carbonization residue is concentrated to a solids mass fraction of 40%–45%, yielding a concentrated portion of the carbonization residue. Taking 1 part by mass of the dried solids from the concentrated portion of the carbonization residue, the concentrated portion of the carbonization residue is mixed with 0.5–1.5 parts by mass of calcined coal gangue powder and 0.1–0.3 parts by mass of desulfurized gypsum to obtain a mixed slurry. The mixed slurry is then mixed with reserved mixing water until the solids mass fraction reaches 50%–65%, yielding a composite slurry of the partially carbonized residue.
[0033] Part of the carbonization residue slurry is premixed with calcined coal gangue powder and desulfurized gypsum, allowing the calcined coal gangue powder to contact the alkaline liquid phase and calcium-containing components in the residue slurry, while the desulfurized gypsum provides sulfate ions. The solids mass fraction of the composite slurry is used to determine its dosage and the amount of water it introduces.
[0034] Preferably, fine aggregate, coarse aggregate, and 60%–70% additional mixing water are mixed to obtain wet aggregate. The wet aggregate is then mixed with silicate cement, granulated blast furnace slag powder, remaining calcined coal gangue powder, and remaining desulfurized gypsum to obtain a powder-aggregate mixture. The powder-aggregate mixture is then sequentially mixed with high-solids content residual slurry, partially carbonized residual slurry composite slurry, polycarboxylate superplasticizer, organosilicon defoamer, and remaining additional mixing water to obtain centrifugal pole concrete.
[0035] The above feeding sequence involves adding the two types of residual slurry to the powder and aggregate mixture in stages, and using the additional mixing water for pre-wetting the aggregate and subsequent mixing, which is combined with the separate metering and moisture deduction of the two types of residual slurry.
[0036] Preferably, the concrete for the centrifugal pole is loaded into the pole mold and centrifuged in stages. The amount of water discharged is obtained by subtracting the corresponding amount of dried solids from the wet mass of the discharged slurry; the amount of water discharged is obtained by subtracting the cumulative amount of water discharged from the total amount of water input; the estimated amount of water remaining in the mold is obtained by subtracting the cumulative amount of water discharged. When the mass fraction of solids discharged is not less than 30% for 30 consecutive seconds, the current centrifugal acceleration is reduced all at once.
[0037] The centrifugal acceleration reduction ratio, preset residual water volume, preset upper limit for solid discharge, and duration of slurry quality change rate should be set to one of the following three sets of parameters: The centrifugal acceleration reduction ratio is 10%, the preset residual water volume is 22 parts by mass, the preset upper limit of solid discharge is 1.0% of the powder material mass, and the duration of the slurry discharge mass change rate is 30s; The centrifugal acceleration reduction rate is 12.5%, the preset residual water volume is 23.5 parts by mass, the preset upper limit of solid discharge is 2.0% of the powder material mass, and the duration of the slurry discharge mass change rate is 45s; The centrifugal acceleration reduction ratio is 15%, the preset residual water volume is 25 parts by mass, the preset upper limit of solid discharge is 3.0% of the powder material mass, and the duration of the slurry discharge mass change rate is 60s.
[0038] The rate of change in slurry quality is the ratio of the absolute value of the difference between the wet slurry quality of the current testing cycle and the wet slurry quality of the previous testing cycle to the wet slurry quality of the previous testing cycle. When the estimated remaining water in the mold reaches the preset remaining water, the cumulative discharged residual slurry dried solid mass is not greater than the preset upper limit of solid discharge, and the rate of change in slurry quality is not greater than 10% within the corresponding duration, centrifugation is stopped, and a centrifugally formed electric rod is obtained.
[0039] By adopting the above technical solution, the estimated remaining water volume within the mold is used to determine the degree of centrifugal dehydration, the cumulative mass of dried solids from the discharged slurry is used to determine the amount of powder material discharged, and the slurry mass change rate is used to determine the slurry discharge status. When the mass fraction of discharged solids reaches the preset condition, the centrifugal acceleration is reduced, and when centrifugation is stopped, the remaining water volume, the amount of solids discharged, and the slurry mass change rate are used simultaneously for judgment.
[0040] This invention provides a low-carbon and environmentally friendly concrete for centrifugal poles and its preparation process. It has the following beneficial effects: 1. This invention uses the moving average of continuous detection values to divert the centrifugal slurry and treats the high-solids-content slurry and low-solids-content slurry separately. The two types of reusable materials are measured according to the mass of solids in the dried slurry, while deducting the moisture they bring in, which can reduce the impact of fluctuations in the mass fraction of solids in the slurry on powder materials and total water consumption.
[0041] 2. This invention determines the partial carbonization endpoint based on the net carbon dioxide absorption and the current titratable alkalinity, and mixes the remaining carbonization slurry with calcined coal gangue powder and desulfurized gypsum in advance. This can retain a certain alkalinity while absorbing some carbon dioxide, providing conditions for the mineral admixtures to participate in the subsequent hydration reaction.
[0042] 3. This invention determines the estimated remaining water volume in the mold based on the wet mass of the discharged slurry and the dry solid mass of the remaining slurry, and controls the centrifugal acceleration and stopping time by combining the cumulative dry solid mass of the discharged slurry and the change rate of the discharged slurry mass. This can take into account both the degree of centrifugal dehydration and the amount of powder material discharged, and reduce the control deviation caused by the determination of a single parameter. Attached Figure Description
[0043] Figure 1 This is a two-parameter scatter plot of some carbonization endpoint control verification tests in the test examples of this invention; Figure 2 This is a scatter plot showing the consistency of residual water volume in the mold during the centrifugal slurry discharge mass balance verification test in the test examples of this invention. Figure 3 This is a box plot of the concrete compressive strength test of the centrifugal pole in the test examples of the present invention. Detailed Implementation
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the preparation examples, comparative examples, test examples, and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] The main raw materials and reagents used are sourced and specified as follows. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0046] The silicate cement is P·Ⅱ52.5 grade silicate cement, CAS number 65997-15-1, with sulfur trioxide content not exceeding 3.5%, chloride ion content not exceeding 0.06%, and alkali content (in Na2O equivalent) not exceeding 0.80%.
[0047] The granulated blast furnace slag powder is S95 grade granulated blast furnace slag powder with a moisture content of no more than 1.0%, a sulfur trioxide content of no more than 4.0%, a chloride ion content of no more than 0.06%, and a loss on ignition of no more than 3.0%.
[0048] The raw material for coal gangue is a mixture of coal gangue minerals containing kaolinite, wherein the kaolinite content is not less than 30%, the total sulfur content is not more than 1.0%, and the chloride ion content is not more than 0.06%.
[0049] Desulfurized gypsum is flue gas desulfurization gypsum that has undergone dehydration, drying and homogenization treatment, and its main component is calcium sulfate dihydrate.
[0050] The fine aggregate is natural river sand with a mud content of no more than 2.0%, a chloride ion content of no more than 0.02%, and a nominal particle size of no more than 5 mm.
[0051] Polycarboxylate superplasticizer is a commercially available ether-based polycarboxylate superplasticizer. Polycarboxylate superplasticizer is measured by solid mass, and its water content is included in the total water content.
[0052] The silicone defoamer is a commercially available water-based silicone defoamer. The silicone defoamer is measured by the mass of its active ingredient, and the water content is included in the total water volume.
[0053] High-solids residue refers to centrifugal residue discharged during the production of centrifugal poles, which, after temperature compensation and density and solids mass fraction calibration, has a solids mass fraction of not less than 30%.
[0054] Low-solids residue is centrifugal residue discharged during the production of centrifugal poles, which, after temperature compensation and density and solids mass fraction calibration, has a solids mass fraction of no more than 25%.
[0055] Preparation Example 1: This preparation example provides a method for preparing calcined coal gangue powder, including the following steps: (1) The coal gangue raw material containing kaolinite is crushed to a particle size of no more than 10 mm to obtain coal gangue particles.
[0056] (2) Dry the coal gangue particles at 105℃ until the moisture content is no more than 1.0% to obtain dried coal gangue particles.
[0057] (3) The dry coal gangue particles are heated to 650°C at an equivalent heating rate of 5°C / min and held for 30 min to obtain coal gangue calcined material.
[0058] (4) Cool the coal gangue calcined material to below 80°C to obtain cooled coal gangue calcined material.
[0059] (5) Grind the cooled coal gangue calcined material to a specific surface area of 450 m². 2 / kg, to obtain the calcined coal gangue powder of Preparation Example 1.
[0060] Preparation Example 2: This preparation example provides a method for preparing calcined coal gangue powder, including the following steps: (1) The coal gangue raw material containing kaolinite is crushed to a particle size of no more than 10 mm to obtain coal gangue particles.
[0061] (2) Dry the coal gangue particles at 112℃ until the moisture content is no more than 1.0% to obtain dried coal gangue particles.
[0062] (3) The dry coal gangue particles are heated to 725℃ at an equivalent heating rate of 12℃ / min and held for 75min to obtain coal gangue calcined material.
[0063] (4) Cool the coal gangue calcined material to below 80°C to obtain cooled coal gangue calcined material.
[0064] (5) Grind the cooled coal gangue calcined material to a specific surface area of 550 m². 2 / kg, to obtain the calcined coal gangue powder of Preparation Example 2.
[0065] Preparation Example 3: This preparation example provides a method for preparing calcined coal gangue powder, including the following steps: (1) The coal gangue raw material containing kaolinite is crushed to a particle size of no more than 10 mm to obtain coal gangue particles.
[0066] (2) Dry the coal gangue particles at 120°C until the moisture content is no more than 1.0% to obtain dried coal gangue particles.
[0067] (3) The dry coal gangue particles are heated to 800℃ at an equivalent heating rate of 20℃ / min and held for 120min to obtain coal gangue calcined material.
[0068] (4) The coal gangue calcined material is indirectly water-cooled to below 80°C to obtain cooled coal gangue calcined material.
[0069] (5) Grind the cooled coal gangue calcined material to a specific surface area of 650 m². 2 / kg, to obtain the calcined coal gangue powder of Preparation Example 3.
[0070] Preparation Example 4: This preparation example provides a method for preparing a partially carbonized residual slurry composite slurry, including the following steps: (1) Mix the low solid content slurry with 25% solid mass fraction with mixing water until the solid mass fraction is 15% to obtain carbonized raw material slurry.
[0071] (2) Divide the carbonization raw material slurry into two parts to obtain the material for benchmark determination and the material for partial carbonization treatment.
[0072] (3) The material for the benchmark determination is controlled at 20℃ and stirred with a stirrer blade linear velocity of 1.5 m / s. The gas with a carbon dioxide volume fraction of 5% is introduced at a speed of 0.05 Nm. 3 / min·m 3 The material used for benchmark testing is introduced; when the net increase in carbon dioxide absorption over 30 minutes is not greater than 1% of the previous cumulative net carbon dioxide absorption, and the pH value is maintained between 8.5 and 9.5, the cumulative net carbon dioxide absorption corresponding to the unit of residual slurry dried solid is determined as the benchmark value for fully carbonized carbon dioxide absorption.
[0073] (4) Obtain a residual slurry sample from the material used for partial carbonization treatment, and titrate the residual slurry sample with 0.10 mol / L hydrochloric acid to a pH value of 8.3 ± 0.1 to obtain the titratable alkalinity before carbonization.
[0074] (5) The material for partial carbonization is controlled at 20°C and stirred at a stirrer blade tip linear velocity of 1.5 m / s. Gas with a carbon dioxide volume fraction of 5% is introduced at a speed of 0.05 Nm. 3 / min·m 3Partial carbonization treatment material is introduced; during the carbonization process, residual slurry samples are periodically obtained and titrated with 0.10 mol / L hydrochloric acid until the pH value is 8.3±0.1 to obtain the current titratable alkalinity; when the net carbon dioxide absorption corresponding to the unit residual slurry drying solid is 30% to 35% of the carbon dioxide absorption benchmark value of complete carbonization, and the current titratable alkalinity is 55% to 60% of the titratable alkalinity before carbonization, the gas introduction is stopped and stirring is continued for 5 minutes to obtain partially carbonized residual slurry.
[0075] (6) Concentrate part of the carbonized residue to a solid mass fraction of 40% to obtain concentrated part of the carbonized residue.
[0076] (7) Take the solid residue from the concentrated carbonized residue as 1 part by mass, mix the concentrated carbonized residue with 0.5 parts by mass of calcined coal gangue powder from Preparation Example 1 and 0.1 parts by mass of desulfurized gypsum, and stir at a stirrer blade tip linear velocity of 1.0 m / s for 2 min to obtain a mixed slurry.
[0077] (8) Mix the mixed slurry with the reserved mixing water until the solid mass fraction is 50% to obtain the partially carbonized residual slurry composite slurry of Preparation Example 4.
[0078] Preparation Example 5: This preparation example provides a method for preparing a partially carbonized residual slurry composite slurry, including the following steps: (1) Mix the low solid content slurry with 25% solid mass fraction with mixing water until the solid mass fraction is 20% to obtain carbonized raw material slurry.
[0079] (2) Divide the carbonization raw material slurry into two parts to obtain the material for benchmark determination and the material for partial carbonization treatment.
[0080] (3) The material for the benchmark determination is controlled at 28℃ and stirred with a stirrer blade linear velocity of 2.5 m / s. The gas with a carbon dioxide volume fraction of 50% is introduced at a speed of 0.15 Nm. 3 / min·m 3 The material used for benchmark testing is introduced; when the net increase in carbon dioxide absorption over 30 minutes is not greater than 1% of the previous cumulative net carbon dioxide absorption, and the pH value is maintained between 8.5 and 9.5, the cumulative net carbon dioxide absorption corresponding to the unit of residual slurry dried solid is determined as the benchmark value for fully carbonized carbon dioxide absorption.
[0081] (4) Obtain a residual slurry sample from the material used for partial carbonization treatment, and titrate the residual slurry sample with 0.10 mol / L hydrochloric acid to a pH value of 8.3 ± 0.1 to obtain the titratable alkalinity before carbonization.
[0082] (5) The material for partial carbonization is controlled at 28℃ and stirred at a stirrer blade tip linear velocity of 2.5 m / s. Gas with a carbon dioxide volume fraction of 50% is introduced at a speed of 0.15 Nm. 3 / min·m 3 Partial carbonization treatment material is introduced; during the carbonization process, residual slurry samples are periodically obtained and titrated with 0.10 mol / L hydrochloric acid until the pH value is 8.3±0.1 to obtain the current titratable alkalinity; when the net carbon dioxide absorption corresponding to the unit residual slurry drying solid is 38% to 42% of the carbon dioxide absorption benchmark value of complete carbonization, and the current titratable alkalinity is 48% to 52% of the titratable alkalinity before carbonization, the gas introduction is stopped and stirring is continued for 8 minutes to obtain partially carbonized residual slurry.
[0083] (6) Concentrate part of the carbonized residue to a solid mass fraction of 40% to obtain concentrated part of the carbonized residue.
[0084] (7) Take the solid residue from the concentrated carbonized residue as 1 part by mass, mix the concentrated carbonized residue with 1.0 part by mass of calcined coal gangue powder from Preparation Example 2 and 0.2 part by mass of desulfurized gypsum, and stir at a stirrer blade tip linear velocity of 1.8 m / s for 3 min to obtain a mixed slurry.
[0085] (8) Mix the mixed slurry with the reserved mixing water until the solid mass fraction is 57.5% to obtain the partially carbonized residual slurry composite slurry of Preparation Example 5.
[0086] Preparation Example 6: This preparation example provides a method for preparing a partially carbonized residual slurry composite slurry, including the following steps: (1) Use the low solid content slurry with a solid mass fraction of 25% as the carbonization raw material slurry.
[0087] (2) Divide the carbonization raw material slurry into two parts to obtain the material for benchmark determination and the material for partial carbonization treatment.
[0088] (3) The material for the benchmark determination is controlled at 35℃ and stirred with a stirrer blade linear velocity of 3.5 m / s. The gas with a carbon dioxide volume fraction of 100% is introduced at a speed of 0.30 Nm. 3 / min·m 3 The material used for benchmark testing is introduced; when the net increase in carbon dioxide absorption over 30 minutes is not greater than 1% of the previous cumulative net carbon dioxide absorption, and the pH value is maintained between 8.5 and 9.5, the cumulative net carbon dioxide absorption corresponding to the unit of residual slurry dried solid is determined as the benchmark value for fully carbonized carbon dioxide absorption.
[0089] (4) Obtain a residual slurry sample from the material used for partial carbonization treatment, and titrate the residual slurry sample with 0.10 mol / L hydrochloric acid to a pH value of 8.3 ± 0.1 to obtain the titratable alkalinity before carbonization.
[0090] (5) The material for partial carbonization is controlled at 35°C and stirred at a stirrer blade tip linear velocity of 3.5 m / s. The gas with a carbon dioxide volume fraction of 100% is introduced at a speed of 0.30 Nm. 3 / min·m 3 Partial carbonization treatment material is introduced; during the carbonization process, residual slurry samples are periodically obtained and titrated with 0.10 mol / L hydrochloric acid until the pH value is 8.3 ± 0.1 to obtain the current titratable alkalinity; when the net carbon dioxide absorption corresponding to the unit residual slurry drying solid is 45% to 50% of the carbon dioxide absorption benchmark value of complete carbonization, and the current titratable alkalinity is 40% to 45% of the titratable alkalinity before carbonization, the gas introduction is stopped and stirring is continued for 10 minutes to obtain partially carbonized residual slurry.
[0091] (6) Concentrate part of the carbonized residue to a solid mass fraction of 45% to obtain concentrated part of the carbonized residue.
[0092] (7) Take the solid residue from the concentrated carbonized residue as 1 part by mass, mix the concentrated carbonized residue with 1.5 parts by mass of calcined coal gangue powder from Preparation Example 3 and 0.3 parts by mass of desulfurized gypsum, and stir at a stirrer blade tip linear velocity of 2.5 m / s for 4 min to obtain a mixed slurry.
[0093] (8) Mix the mixed slurry with the reserved mixing water until the solid mass fraction is 65% to obtain the partially carbonized residual slurry composite slurry of Preparation Example 6.
[0094] In the following embodiments, a calibration relationship between the density and solid mass fraction of centrifuged residual slurry was established using a drying method, and the density detected by the online density meter was converted into solid mass fraction based on the calibration relationship. The allowable reuse time for high-solids-content residual slurry is the shorter of 30 minutes from its generation and one-third of the measured initial setting time of the corresponding concrete. The corresponding dry solid mass of the residual slurry was determined based on the wet mass and solid mass fraction of the discharged slurry. The rate of change in discharged slurry mass is the percentage obtained by dividing the absolute value of the difference between the wet mass of the discharged slurry in the current testing cycle and the wet mass of the discharged slurry in the previous testing cycle by the wet mass of the discharged slurry in the previous testing cycle.
[0095] Example 1: This embodiment provides a low-carbon and environmentally friendly process for preparing centrifugal pole concrete, including the following steps: (1) The solid content of the centrifuged slurry discharged from different production batches was tested at 1-5s intervals. The centrifuged slurry with a moving average of 5 consecutive test values of not less than 30% was diverted as high solid content slurry, the centrifuged slurry with a moving average of not more than 25% was diverted as low solid content slurry, and the centrifuged slurry with a moving average of more than 25% and less than 30% was diverted as intermediate solid content slurry. If the number of consecutive test values was less than 5, the centrifuged slurry was diverted as intermediate solid content slurry, and the intermediate solid content slurry was homogenized and retested. The high solid content slurry with a solid content of 50% and within the allowable reuse time was reserved, and the low solid content slurry with a solid content of 25% was processed according to Preparation Example 4 to obtain a composite slurry of high solid content slurry to be used and partially carbonized slurry of Preparation Example 4.
[0096] (2) 58 parts by weight of silicate cement, 26.8 parts by weight of granulated blast furnace slag powder, 10 parts by weight of calcined coal gangue powder, 3 parts by weight of high-solids content residual slurry dried solids, 2 parts by weight of partially carbonized residual slurry dried solids, and 0.2 parts by weight of desulfurized gypsum were mixed to prepare 100 parts by weight of powder material, thus obtaining the powder material mix. The powder material mix was combined with 125 parts by weight of saturated surface-dried fine aggregate, 250 parts by weight of coarse aggregate, 25 parts by weight of total water, 0.18 parts by weight of polycarboxylate superplasticizer solids, and 0.01 parts by weight of organosilicon defoamer active ingredients to obtain concrete mix.
[0097] (3) Based on the concrete mix design and the measured solid mass fraction, the amount of wet slurry with high solid content was determined to be 6 parts by mass, and the amount of composite slurry with partial carbonization residue in Preparation Example 4 was determined to be 6.4 parts by mass. The water content in the high solid content slurry, the composite slurry with partial carbonization residue in Preparation Example 4, the polycarboxylate superplasticizer and the silicone defoamer was deducted from the total water content to obtain 18.51 parts by mass of additional mixing water.
[0098] (4) Mix fine aggregate, coarse aggregate and 60% of newly added mixing water for 20s to obtain wet aggregate; mix wet aggregate with silicate cement, granulated blast furnace slag powder and the remaining 9 parts by mass of calcined coal gangue powder for 30s to obtain powder and aggregate mixture; mix powder and aggregate mixture with high solids content residual slurry for 30s, then mix with part of carbonized residual slurry composite slurry prepared in Example 4 for 20s, and finally mix with polycarboxylate superplasticizer, organosilicon defoamer and the remaining newly added mixing water for 60s to obtain centrifugal pole concrete.
[0099] (5) The concrete for the centrifugal pole is loaded into the pole mold and centrifuged sequentially at 1g for 2min, 10g for 2min, and 30g. The amount of water discharged is obtained by subtracting the corresponding amount of dried solids from the wet mass of the discharged slurry. The amount of water discharged is then obtained by subtracting the cumulative amount of water discharged from the total amount of water input. The estimated amount of water remaining in the mold is obtained by subtracting the cumulative amount of water discharged. When the mass fraction of the discharged solids is not less than 30% for 30s, the current centrifugal acceleration is reduced by 10% at one time. When the estimated amount of water remaining in the mold reaches 22 parts by mass, the cumulative amount of dried solids discharged is not greater than 1.0% of the mass of the powder material, and the mass change rate of the discharged slurry is not greater than 10% for 30s, the centrifugation is stopped and the centrifugally formed pole is obtained.
[0100] (6) The centrifugally formed pole is left to stand still for 2 hours, then heated to 55°C at a rate of no more than 15°C / h and kept at a constant temperature for 6 hours. Then it is cooled down at a rate of no more than 15°C / h and demolded. At the same time, the internal temperature of the concrete is controlled to be no higher than 60°C to obtain the centrifugally formed pole.
[0101] Example 2: This embodiment provides a low-carbon and environmentally friendly process for preparing centrifugal pole concrete, including the following steps: (1) The solid content of the centrifuged slurry discharged from different production batches was tested at 1-5s intervals. The centrifuged slurry with a moving average of 10 consecutive test values not less than 30% was diverted as high solid content slurry, the centrifuged slurry with a moving average of not more than 25% was diverted as low solid content slurry, and the centrifuged slurry with a moving average of more than 25% and less than 30% was diverted as intermediate solid content slurry. If the number of consecutive test values did not reach 10, the centrifuged slurry was diverted as intermediate solid content slurry, and the intermediate solid content slurry was homogenized and retested. The high solid content slurry with a solid content of 45% and within the allowable reuse time was reserved, and the low solid content slurry with a solid content of 25% was processed according to Preparation Example 5 to obtain a composite slurry of high solid content slurry to be used and partially carbonized slurry of Preparation Example 5.
[0102] (2) Prepare 100 parts by weight of powder material by mixing 55 parts by weight of silicate cement, 25 parts by weight of granulated blast furnace slag powder, 10 parts by weight of calcined coal gangue powder, 5 parts by weight of high solids content residual slurry dried solids, 4 parts by weight of partially carbonized residual slurry dried solids, and 1 part by weight of desulfurized gypsum to obtain powder material batching. Combine the powder material batching with 135 parts by weight of fine aggregate in saturated surface-dry state, 270 parts by weight of coarse aggregate, 27 parts by weight of total water, 0.24 parts by weight of polycarboxylate superplasticizer solids, and 0.02 parts by weight of organosilicon defoamer active ingredients to obtain concrete batching.
[0103] (3) Based on the concrete mix design and the measured solid mass fraction, the amount of wet slurry with high solid content was determined to be 11.11 parts by mass, and the amount of composite slurry with partial carbonization residue in Preparation Example 5 was determined to be 15.30 parts by mass. The water content in the high solid content slurry, the composite slurry with partial carbonization residue in Preparation Example 5, the polycarboxylate superplasticizer and the silicone defoamer was deducted from the total water content to obtain 13.98 parts by mass of additional mixing water.
[0104] (4) Fine aggregate, coarse aggregate and 65% of newly added mixing water are mixed for 25s to obtain wet aggregate; wet aggregate is mixed with silicate cement, granulated blast furnace slag powder, 6 parts by mass of calcined coal gangue powder and 0.2 parts by mass of desulfurized gypsum for 38s to obtain powder and aggregate mixture; powder and aggregate mixture is mixed with high solids content residual slurry for 38s, then mixed with part of carbonized residual slurry composite slurry of Preparation Example 5 for 25s, and finally mixed with polycarboxylate superplasticizer, organosilicon defoamer and the remaining newly added mixing water for 75s to obtain centrifugal pole concrete.
[0105] (5) The concrete for the centrifugal pole is loaded into the pole mold and centrifuged sequentially at 2g for 3min, 15g for 3.5min, and 37.5g. The amount of water discharged is obtained by subtracting the corresponding amount of dried solids from the wet mass of the discharged slurry. The amount of water discharged is then obtained by subtracting the cumulative amount of water discharged from the total amount of water input. The amount of water remaining in the mold is estimated. When the mass fraction of the discharged solids is not less than 30% for 30s, the current centrifugal acceleration is reduced by 12.5% at one time. When the estimated amount of water remaining in the mold reaches 23.5 parts by mass, the cumulative mass of dried solids discharged is not greater than 2.0% of the mass of the powder material, and the mass change rate of the discharged slurry is not greater than 10% for 45s, the centrifugation is stopped and the centrifugally formed pole is obtained.
[0106] (6) The centrifugally formed pole is left to stand still for 2.5 hours, then heated to 58°C at a rate of no more than 15°C / h and kept at that temperature for 7 hours. Then it is cooled down at a rate of no more than 15°C / h and demolded. At the same time, the internal temperature of the concrete is controlled to be no higher than 60°C to obtain the centrifugally formed pole.
[0107] Example 3: This embodiment provides a low-carbon and environmentally friendly process for preparing centrifugal pole concrete, including the following steps: (1) The solid content of the centrifugal slurry discharged from different production batches was tested at 1-5s intervals. The centrifugal slurry with a moving average of 15 consecutive test values of not less than 30% was diverted as high solid content slurry, the centrifugal slurry with a moving average of not more than 25% was diverted as low solid content slurry, and the centrifugal slurry with a moving average of more than 25% and less than 30% was diverted as intermediate solid content slurry. If the number of consecutive test values did not reach 15, the centrifugal slurry was diverted as intermediate solid content slurry, and the intermediate solid content slurry was homogenized and retested. The high solid content slurry with a solid content of 60% and within the allowable reuse time was reserved, and the low solid content slurry with a solid content of 25% was processed according to Preparation Example 6 to obtain a composite slurry of high solid content slurry to be used and partially carbonized slurry of Preparation Example 6.
[0108] (2) 53 parts by weight of silicate cement, 24 parts by weight of granulated blast furnace slag powder, 10.5 parts by weight of calcined coal gangue powder, 6 parts by weight of high-solids content residual slurry dried solids, 5 parts by weight of partially carbonized residual slurry dried solids, and 1.5 parts by weight of desulfurized gypsum were mixed to prepare 100 parts by weight of powder material, thus obtaining the powder material mix. The powder material mix was combined with 145 parts by weight of saturated surface-dried fine aggregate, 290 parts by weight of coarse aggregate, 29 parts by weight of total water, 0.30 parts by weight of polycarboxylate superplasticizer solids, and 0.03 parts by weight of organosilicon defoamer active ingredients to obtain concrete mix.
[0109] (3) Based on the concrete mix design and the measured solid mass fraction, the amount of wet slurry with high solid content was determined to be 10 parts by mass, and the amount of composite slurry with partial carbonization residue in Preparation Example 6 was determined to be 21.54 parts by mass. The water content in the high solid content slurry, the composite slurry with partial carbonization residue in Preparation Example 6, the polycarboxylate superplasticizer and the silicone defoamer was deducted from the total water content to obtain 16.94 parts by mass of additional mixing water.
[0110] (4) Mix fine aggregate, coarse aggregate and 70% of newly added mixing water for 30s to obtain wet aggregate; mix wet aggregate with silicate cement, granulated blast furnace slag powder and the remaining 3 parts by mass of calcined coal gangue powder for 45s to obtain powder and aggregate mixture; mix powder and aggregate mixture with high solid content residual slurry for 45s, then mix with part of carbonized residual slurry composite slurry prepared in Example 6 for 30s, and finally mix with polycarboxylate superplasticizer, organosilicon defoamer and the remaining newly added mixing water for 90s to obtain centrifugal pole concrete.
[0111] (5) The concrete for the centrifugal pole is loaded into the pole mold and centrifuged sequentially at 3g for 4min, 20g for 5min, and 45g. The amount of water discharged is obtained by subtracting the corresponding amount of dried solids from the wet mass of the discharged slurry. The amount of water discharged is then obtained by subtracting the cumulative amount of water discharged from the total amount of water input. The amount of water remaining in the mold is estimated. When the mass fraction of the discharged solids is not less than 30% for 30s, the current centrifugal acceleration is reduced by 15% at one time. When the estimated amount of water remaining in the mold reaches 25 parts by mass, the cumulative mass of dried solids discharged is not greater than 3.0% of the mass of the powder material, and the mass change rate of the discharged slurry is not greater than 10% for 60s, the centrifugation is stopped and the centrifugally formed pole is obtained.
[0112] (6) The centrifugally formed pole is left to stand still for 3 hours, then heated to 60°C at a rate of no more than 15°C / h and kept at a constant temperature for 8 hours. Then it is cooled down at a rate of no more than 15°C / h and demolded. At the same time, the internal temperature of the concrete is controlled to be no higher than 60°C to obtain the centrifugally formed pole.
[0113] Comparative Example 1: Compared with Example 2, the difference is that no high solids content residual slurry is added, 5 parts by weight of dried solids of high solids content residual slurry are replaced with 5 parts by weight of silicate cement, and the water introduced by the high solids content residual slurry is made up with newly added mixing water. All other aspects are the same.
[0114] Comparative Example 2: Compared with Example 2, the difference is that 4 parts by mass of dried solid carbonized residual slurry in the partially carbonized residual slurry composite slurry of Example 5 are replaced with 4 parts by mass of silicate cement, while the calcined coal gangue powder, desulfurized gypsum and total water remain unchanged, and the rest are the same.
[0115] Comparative Example 3: Compared with Example 2, the difference is that the low solids content slurry is not partially carbonized, but directly concentrated to a solids mass fraction of 40% and then mixed with calcined coal gangue powder and desulfurized gypsum to prepare a composite slurry. All other aspects are the same.
[0116] Comparative Example 4: Compared with Example 2, the difference is that the net carbon dioxide absorption of the low solids content slurry is controlled to the carbon dioxide absorption benchmark value of complete carbonization, and the composite slurry is prepared after complete carbonization. All other aspects are the same.
[0117] Comparative Example 5: Compared with Example 2, the difference is that in the carbonization process of low solids content slurry, only the pH value reaching 9.0±0.1 is used as the condition for stopping the gas introduction, and the net carbon dioxide absorption and titratable alkalinity are not used to jointly determine the carbonization endpoint. All other aspects are the same.
[0118] Comparative Example 6: Compared with Example 2, the difference is that some of the carbonization residue is not pre-mixed with calcined coal gangue powder and desulfurized gypsum, and some of the carbonization residue, the corresponding mass of calcined coal gangue powder and desulfurized gypsum are added during the concrete mixing stage, while the rest are the same.
[0119] Comparative Example 7: Compared with Example 2, the difference is that when the mass fraction of discharged solids is not less than 30% for 30 consecutive seconds, the centrifugal acceleration is not reduced, and centrifugation continues at the original centrifugal acceleration. All other aspects are the same.
[0120] Comparative Example 8: Compared with Example 2, the difference is that only the estimated remaining water in the mold reaches 23.5 parts by mass as the condition for stopping centrifugation, and the centrifugation endpoint is no longer determined by the cumulative discharged residual slurry dry solid mass and the change rate of slurry mass. All other aspects are the same.
[0121] Comparative Example 9: Compared with Example 2, the difference is that the residual slurry is diverted based on the solid mass fraction obtained from a single test, and the moving average of 10 consecutive test values is not calculated; otherwise, they are the same.
[0122] Test Example 1: (1) The residual slurry diversion method of Examples 1-3 (1) and Comparative Example 9 was used as the experimental object. The high solids content residual slurry, intermediate solids content residual slurry and low solids content residual slurry were added to the feeding container respectively. The discharge flow rate of each feeding container was adjusted according to the same discharge procedure so that the solid mass fraction of the centrifuged residual slurry alternated between 25% and 30%.
[0123] (2) The solid mass fraction of the centrifuged slurry was detected at a period of 2 seconds, and each group of experiments was run for 360 seconds. In Examples 1 to 3, the moving average of 5, 10, and 15 consecutive detection values was used for diversion determination, respectively, while in Comparative Example 9, a single detection value was used for diversion determination. Before the moving average detection value reached the preset number, the centrifuged slurry was diverted into slurry with intermediate solid content.
[0124] (3) When the test result is not greater than 25%, the centrifugal slurry is diverted into low solids content slurry; when the test result is not less than 30%, the centrifugal slurry is diverted into high solids content slurry; when the test result is greater than 25% and less than 30%, the centrifugal slurry is diverted into intermediate solids content slurry.
[0125] (4) Residual slurry samples were obtained synchronously in each testing cycle. The solid mass fraction was determined by the drying method, and the reference category was determined. The diversion judgment result was compared with the reference category, and the number of diversion switching, the number of erroneous diversions, and the judgment accuracy were counted. The time interval from the moment when the reference category changed to the time interval when the diversion judgment result was consistent with the reference category for three consecutive testing cycles was determined as the judgment lag time.
[0126] (5) Each residual slurry diversion method was tested in parallel three times and the arithmetic mean was calculated. The average of the number of diversion switching and the number of erroneous diversions was rounded to the nearest integer, and the average of the judgment accuracy and judgment lag time was rounded to one decimal place. The experimental results are shown in Table 1.
[0127] Table 1. Results of residual slurry diversion stability test:
[0128] Note: The window number is the number of consecutive detection values used in the moving average calculation; the instantaneous value is a single detection value.
[0129] According to Table 1, by comparing the moving average judgment results and instantaneous value judgment results with the reference category determined by the drying method, the number of diversion switching times and the number of erroneous diversions in Examples 1-3 were all lower than those in Comparative Example 9, indicating that the moving average of continuous detection values can reduce the impact of instantaneous fluctuations in solid mass fraction on residual slurry diversion. There are differences in the number of diversion switching times and judgment lag times corresponding to different window numbers, with Example 2 having fewer erroneous diversions and a judgment lag time between that of Examples 1 and 3. The above results can be used to demonstrate the feasibility of using the moving average of 5-15 consecutive detection values for residual slurry diversion.
[0130] Test Example 2: (1) The partial carbonized residue of Examples 4 to 6, the uncarbonized residue of Comparative Example 3, the fully carbonized residue of Comparative Example 4 and the carbonized residue of Comparative Example 5 were used as experimental objects, and three parallel samples were set up for each experimental object.
[0131] (2) Record the intake volume, exhaust volume and inlet and outlet carbon dioxide volume fraction of each parallel sample. Determine the net carbon dioxide absorption based on the difference between the cumulative intake carbon dioxide and the cumulative exhaust carbon dioxide, and calculate the ratio of the net carbon dioxide absorption to the complete carbon dioxide absorption benchmark value to obtain the net carbon dioxide absorption ratio.
[0132] (3) Take the residual slurry sample from each parallel sample, and titrate it with 0.10 mol / L hydrochloric acid to a pH value of 8.3 ± 0.1. Calculate the proportion of titratable alkalinity to titratable alkalinity before carbonization based on the amount of hydrochloric acid consumed per unit of residual slurry drying solid, obtain the titratable alkalinity retention ratio, and determine the endpoint pH value.
[0133] (4) Calculate the arithmetic mean and standard deviation of the test results for the three parallel samples. The experimental results are shown in Table 2 and... Figure 1 As shown.
[0134] Table 2. Carbonization endpoint parameters for different treatment methods:
[0135] Note: The absorption ratio is the ratio of net carbon dioxide absorption to the baseline value of carbon dioxide absorption in complete carbonization; the alkalinity ratio is the ratio of titratable alkalinity to the titratable alkalinity before carbonization.
[0136] See appendix Figure 1 The figure shows the partial carbonized residue of Preparation Examples 4-6, the uncarbonized residue of Comparative Example 3, the fully carbonized residue of Comparative Example 4, and the carbonized residue of Comparative Example 5; the horizontal axis represents the net carbon dioxide absorption ratio, and the vertical axis represents the titratable alkalinity retention ratio.
[0137] According to Table 2 and Figure 1 By simultaneously measuring the net carbon dioxide absorption ratio and the titratable alkalinity retention ratio, the parallel samples prepared in Examples 4-6 were within their respective predefined partial carbonization ranges, indicating that the two parameters can be used together to define the partial carbonization endpoint of the low-solids slurry. No carbon dioxide absorption occurred in Comparative Example 3, while the net carbon dioxide absorption ratios of Comparative Examples 4 and 5 were close to the carbon dioxide absorption benchmark value for complete carbonization, and their titratable alkalinity retention ratios were relatively low.
[0138] The above comparison shows that the net carbon dioxide absorption and titratable alkalinity can be used to distinguish between uncarbonized, partially carbonized and nearly fully carbonized treatment states, and provide a basis for the endpoint control of partially carbonized slurry.
[0139] Test Example 3: (1) The cementitious material systems corresponding to Examples 1-3 and Comparative Examples 1-6 were used as experimental objects. Test slurries were prepared according to the mass ratio of powder materials, high solids content residual slurry, partially carbonized residual slurry composite slurry, polycarboxylate superplasticizer, organosilicon defoamer and total water in each scheme, without adding fine aggregate and coarse aggregate.
[0140] (2) Mix the raw materials of each group according to the order of feeding in the corresponding scheme, take 10.0g of test slurry and put it into a sealed sample bottle, and continuously measure the hydration heat flow from 0 to 72h at 25℃, and use the mass of powder material as the normalization benchmark.
[0141] (3) The end time of the induction period, the occurrence time of the main exothermic peak, and the peak value of the main exothermic peak were determined based on the hydration heat flow detection results. The cumulative heat release over 72 hours was obtained by integration. Each group was tested in parallel three times, and the arithmetic mean and standard deviation of each parameter were calculated. The experimental results are shown in Table 3.
[0142] Table 3. Isothermal hydration calorimetry results of the cementitious material system:
[0143] Note: The induction period is the end time of the induction period; the main peak is the main exothermic hydration peak that appears after the induction period ends.
[0144] According to Table 3, by comparing the induction period, main exothermic peak, and cumulative heat release over 72 hours for each cementitious material system, Examples 1-3 all exhibited a continuous hydration exothermic process, indicating that the cementitious material system could still undergo hydration reaction after the addition of high-solids-content residual slurry and partially carbonized residual slurry composite slurry. Comparative Examples 4 and 5 had longer induction periods than Example 2, and lower cumulative heat release over 72 hours than Example 2, suggesting that the near-complete carbonization treatment state affects the participation of residual slurry in subsequent hydration reactions.
[0145] The comparison between Example 2 and Comparative Example 6 illustrates the correlation between the pre-prepared partially carbonized residual slurry composite slurry and the hydration process of the cementitious materials. Comparative Examples 1 and 2, which replaced the corresponding residual slurry drying solids with silicate cement, showed slightly higher cumulative heat release over 72 hours compared to Example 2, consistent with the hydration heat release characteristics after increasing the amount of silicate cement. These results demonstrate that the partial carbonization endpoint control and the preparation steps of the partially carbonized residual slurry composite slurry are based on hydration reactions.
[0146] Test Example 4: (1) Taking the centrifugation process of Examples 1-3, Comparative Examples 7 and 8 as the experimental objects, three electric pole test molds of the same specifications were set up in each group, and the mass of the empty mold, the total amount of water added and the total mass of dry materials added were recorded.
[0147] (2) Centrifuge according to the corresponding conditions of each group, collect the centrifuged slurry discharged during the centrifugation process using a weighing container, and determine the cumulative wet mass of discharged slurry and the cumulative dry solid mass of discharged slurry. Subtract the cumulative dry solid mass of discharged slurry from the cumulative wet mass of discharged slurry to obtain the cumulative discharged water volume; subtract the cumulative discharged water volume from the total water input to obtain the estimated remaining water volume in the mold.
[0148] (3) After stopping centrifugation, weigh the total mass of the mold and the material inside the mold. Subtract the cumulative mass of the dried solids from the discharged slurry from the total mass of the input dry material to obtain the mass of the remaining dry material inside the mold; subtract the mass of the empty mold and the mass of the remaining dry material inside the mold from the total mass of the mold and the material inside the mold to obtain the actual amount of water remaining in the mold, and record the rate of change of the discharged slurry mass when centrifugation stops.
[0149] (4) Calculate the arithmetic mean of the results of the three parallel experiments, and calculate the absolute value of the difference between the estimated remaining water volume and the actual remaining water volume in the mold in each parallel experiment. The experimental results are shown in Table 4 and... Figure 2 As shown.
[0150] Table 4. Verification results of centrifugal slurry discharge mass balance:
[0151] Note: The data in the table are the arithmetic mean of three parallel experiments. Parts refer to the mass of 100 parts of powder material; total water is the total amount of water added; wet discharge is the cumulative wet mass of discharged slurry; discharged solids is the proportion of the cumulative mass of discharged residual slurry dried solids to the mass of the powder material; estimated water volume is the estimated remaining water volume in the mold; actual water volume is the actual remaining water volume in the mold; absolute error is the average of the absolute values of the differences between the estimated and actual water volumes in each parallel experiment; the rate of change is the rate of change of discharged slurry mass when centrifugation stops.
[0152] See appendix Figure 2 The figure shows the estimated and actual remaining water volume in the molds for each parallel experiment of Examples 1-3, Comparative Examples 7 and 8. The dashed line represents the consistency reference line.
[0153] According to Table 4 and Figure 2 By comparing the estimated residual water volume inside the mold obtained from the mass balance of the slurry discharge side with the actual residual water volume inside the mold obtained from the weighing of the mold side, the absolute error of Examples 1 to 3 was 0.14 to 0.26 parts by mass, indicating that the cumulative wet mass of the discharged slurry and the cumulative dry solid mass of the discharged residual slurry can be used to estimate the residual water volume inside the mold.
[0154] Compared to Example 2, Comparative Example 7 did not perform a centrifugal acceleration reduction operation, resulting in an increase in the cumulative mass of dried solids from the discharged slurry; Comparative Example 8 stopped centrifugation only based on an estimate of the remaining water content within the mold, resulting in an increase in both the cumulative mass of dried solids from the discharged slurry and the rate of change in discharged slurry mass. The above comparisons demonstrate that by combining the reduction condition corresponding to the mass fraction of discharged solids with the estimated remaining water content within the mold, the cumulative mass of dried solids from the discharged slurry, and the rate of change in discharged slurry mass for centrifugal control, both the drainage status and the powder discharge status can be determined simultaneously.
[0155] Test Example 5: (1) Centrifugal rods prepared in Examples 1-3 and Comparative Examples 1-9 were used as experimental objects. Three centrifugal rods were prepared for each group. After demolding, they were cured for 28 days at a temperature of 20±2℃ and a relative humidity of not less than 95%.
[0156] (2) Two concrete core samples were drilled at the same axial position of each centrifugal pole, avoiding the reinforcing bars. The concrete core samples were processed into specimens with a diameter of 50 mm and a height-to-diameter ratio of 1.0. Six concrete core samples were obtained in each group.
[0157] (3) The two bearing surfaces of the concrete core sample are processed to be flat, and the concrete core sample is continuously and uniformly loaded until failure according to the current concrete core sample compressive strength test method. The compressive strength is calculated according to the maximum load, bearing area and the same size conversion rules.
[0158] (4) Calculate the average, minimum, maximum, and coefficient of variation of the compressive strength for each group. The experimental results are shown in Table 5 and... Figure 3 As shown.
[0159] Table 5. Test results of compressive strength of concrete for centrifugal poles:
[0160] Note: Each set of data was calculated from the compressive strength of 6 concrete core samples; the coefficient of variation is the percentage of the standard deviation of the compressive strength to the average strength.
[0161] See appendix Figure 3 The figure shows the compressive strength distribution of six concrete core samples from Examples 1-3 and Comparative Examples 1-9.
[0162] According to Table 5 and Figure 3 By conducting compressive strength tests on concrete core samples obtained from the same location on the centrifuge pole, the coefficients of variation for Examples 1-3 ranged from 1.33% to 1.80%, indicating that the compressive strength within the parameter range of this invention has a certain degree of repeatability. A comparison of Example 2 with Comparative Examples 3-6 can be used to demonstrate that partial carbonation endpoint control and the pre-preparation of the partially carbonized residual slurry composite slurry are related to the formation of compressive strength; a comparison of Example 2 with Comparative Examples 7 and 8 can be used to demonstrate that the centrifugal acceleration reduction operation and the determination of the multi-parameter centrifugal endpoint are related to the retention of powder materials.
[0163] The coefficient of variation of Comparative Example 9 was higher than that of Example 2, indicating that using the moving average of continuous test values for residual slurry diversion is beneficial for controlling the performance dispersion among specimens. Comparative Examples 1 and 2 used silicate cement to replace the dried solids of residual slurry, and their average compressive strength was slightly higher than that of Example 2; Example 2 achieved a similar compressive strength while reducing the amount of silicate cement used.
[0164] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these specific embodiments are merely illustrative examples, and those skilled in the art can omit, substitute, and change the details of the above technical solutions in various ways without departing from the principles and essence of the present invention.
Claims
1. A low-carbon and environmentally friendly concrete centrifugal pole, characterized in that, Made from raw materials comprising the following parts by weight: Based on 100 parts by weight of powder materials, the following components are included: 53-58 parts of silicate cement, 24-26.8 parts of granulated blast furnace slag powder, 10-10.5 parts of calcined coal gangue powder, 3-6 parts of high-solids content residual slurry (the amount of high-solids content residual slurry is based on the dried solids of the high-solids content residual slurry), 2-5 parts of partially carbonized residual slurry composite slurry (the amount of partially carbonized residual slurry composite slurry is based on the dried solids of the partially carbonized residual slurry), 0.2-1.5 parts of desulfurized gypsum, 125-145 parts of fine aggregate, 250-290 parts of coarse aggregate, 25-29 parts of total water, 0.18-0.30 parts of polycarboxylate superplasticizer solids, and 0.01-0.03 parts of the effective component of organosilicon defoamer.
2. The centrifugal pole concrete according to claim 1, characterized in that, Made from raw materials comprising the following parts by weight: Based on 100 parts by weight of powder materials, the following are included: 55 parts of silicate cement, 25 parts of granulated blast furnace slag powder, 10 parts of calcined coal gangue powder, 5 parts of high-solids content residual slurry (the amount of high-solids content residual slurry is calculated based on the dried solids of the high-solids content residual slurry), 4 parts of partially carbonized residual slurry composite slurry (the amount of partially carbonized residual slurry composite slurry is calculated based on the dried solids of the partially carbonized residual slurry), 1 part of desulfurized gypsum, 135 parts of fine aggregate, 270 parts of coarse aggregate, 27 parts of total water, 0.24 parts of polycarboxylate superplasticizer solids, and 0.02 parts of the effective component of organosilicon defoamer.
3. The centrifugal pole concrete according to claim 1, characterized in that, The high-solids content slurry is obtained by continuously detecting the solids mass fraction of the centrifuged slurry and diverting it according to the moving average of the continuous detection values, and the high-solids content slurry is within the allowable reuse time. The partially carbonized residual slurry composite slurry is prepared by mixing low-solids residual slurry with calcined coal gangue powder and desulfurized gypsum after partial carbonization and concentration. During the partial carbonization process, the net carbon dioxide absorption is detected and the current titratable alkalinity is determined. The partial carbonization endpoint is determined based on the net carbon dioxide absorption and the current titratable alkalinity.
4. The centrifugal pole concrete according to claim 1, characterized in that, The calcined coal gangue powder is obtained by calcining coal gangue raw materials containing kaolinite at 650-800℃ for 30-120 minutes and then grinding them. The solid content of the dried residue from the concentrated partial carbonization residue slurry is 1 part by weight. The calcined coal gangue powder in the partial carbonization residue slurry composite slurry is 0.5 to 1.5 parts by weight, the desulfurized gypsum is 0.1 to 0.3 parts by weight, and the solid content of the partial carbonization residue slurry composite slurry is 50% to 65% by weight.
5. A preparation process for low-carbon and environmentally friendly centrifugal pole concrete as described in any one of claims 1-4, characterized in that, Includes the following steps: The solids mass fraction of the centrifuged slurry is continuously monitored, and the slurry is split according to the following rules based on the moving average of the continuous monitoring values: Slurry with a content not less than the preset high solids content threshold is classified as high solids content slurry; slurry with a content not greater than the preset low solids content threshold is classified as low solids content slurry; and slurry with a content between the two thresholds is classified as intermediate solids content slurry. The high-solids content slurry is kept on standby within the allowable reuse time. The low-solids content slurry is partially carbonized and concentrated, and then stirred with calcined coal gangue powder and desulfurized gypsum to obtain a partially carbonized slurry composite slurry. Based on the mass of the dried solids of the high-solids content residual slurry and the mass of the dried solids of the partially carbonized residual slurry in the concrete mix, and in combination with the measured solid mass fraction, the wet addition amount of the high-solids content residual slurry and the addition amount of the partially carbonized residual slurry composite slurry are determined. The water content of the high-solids content residual slurry, the partially carbonized residual slurry composite slurry, the polycarboxylate superplasticizer and the silicone defoamer are deducted from the total water volume to obtain the additional mixing water. The high-solids-content residual slurry, the partially carbonized residual slurry composite slurry, and the added mixing water are mixed with the remaining concrete raw materials to obtain centrifugal pole concrete.
6. The preparation process of centrifugal pole concrete according to claim 5, characterized in that, The detection cycle for the solid mass fraction is 1–5 seconds, the moving average is calculated using 5–15 consecutive detection values, the preset high solid content threshold is 30%, and the preset low solid content threshold is 25%. When the continuous detection value does not reach the preset number, the centrifugal slurry is diverted into the intermediate solids content slurry, and the intermediate solids content slurry is homogenized and then re-detected. The allowable reuse time is the shorter of 30 minutes from the time of generation and one-third of the measured initial setting time of the corresponding concrete.
7. The preparation process of centrifugal pole concrete according to claim 5, characterized in that, The low-solids slurry is divided into material for benchmark testing and material for partial carbonization treatment. Gas containing carbon dioxide is introduced into the material used for the benchmark determination. When the net carbon dioxide absorption corresponding to the unit increase in the unit residual slurry drying solids for 30 minutes is not greater than 1% of the previous cumulative net carbon dioxide absorption, and the pH value is maintained between 8.5 and 9.5, the cumulative net carbon dioxide absorption corresponding to the unit residual slurry drying solids is determined as the benchmark value for fully carbonized carbon dioxide absorption. The ratio of the net carbon dioxide absorption corresponding to the unit residual slurry drying solid to the carbon dioxide absorption benchmark value of complete carbonization and the ratio of the current titratable alkalinity to the titratable alkalinity before carbonization are respectively 30%~35% and 55%~60%, 38%~42% and 48%~52%, or 45%~50% and 40%~45%.
8. The preparation process of centrifugal pole concrete according to claim 5, characterized in that, The carbonized residue is concentrated to a solid mass fraction of 40% to 45% to obtain concentrated carbonized residue. Taking the dried solids of the concentrated partial carbonization slurry as 1 part by mass, the concentrated partial carbonization slurry is mixed with 0.5 to 1.5 parts by mass of the calcined coal gangue powder and 0.1 to 0.3 parts by mass of the desulfurized gypsum to obtain a mixed slurry; The mixed slurry is stirred with the reserved mixing water until the solid mass fraction is 50% to 65% to obtain the partially carbonized residual slurry composite slurry.
9. The preparation process of centrifugal pole concrete according to claim 5, characterized in that, The remaining concrete raw materials include silicate cement, granulated blast furnace slag powder, residual calcined coal gangue powder, residual desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylate superplasticizer, and organosilicon defoamer. The fine aggregate, the coarse aggregate, and 60%–70% of the newly added mixing water are stirred to obtain wet aggregate. The wet aggregate is then stirred with the silicate cement, the granulated blast furnace slag powder, the remaining calcined coal gangue powder, and the remaining desulfurized gypsum to obtain a powder and aggregate mixture. The powder and aggregate mixture is sequentially mixed with the high solids content residual slurry, the partially carbonized residual slurry composite slurry, the polycarboxylate superplasticizer, the organosilicon defoamer, and the remaining added mixing water to obtain the centrifugal pole concrete.
10. The preparation process of centrifugal pole concrete according to claim 5, characterized in that, It also includes the step of loading the centrifugal pole concrete into the pole mold and centrifuging it in stages: Subtract the corresponding dry solid mass of the discharged slurry from the wet mass of the discharged slurry to obtain the discharged water volume. Subtract the cumulative discharged water volume from the total water input to obtain the estimated remaining water volume in the mold. When the mass fraction of discharged solid mass is not less than 30% for 30 consecutive seconds, the current centrifugal acceleration is reduced all at once. The centrifugal acceleration reduction ratio, preset residual water volume, preset upper limit of solid discharge, and duration of slurry mass change rate are set at 10%, 22 parts by mass, 1.0% of the powder material mass, and 30s, or at 12.5%, 23.5 parts by mass, 2.0% of the powder material mass, and 45s, or at 15%, 25 parts by mass, 3.0% of the powder material mass, and 60s. The mass of the powder material is the total mass of the silicate cement, the granulated blast furnace slag powder, the calcined coal gangue powder, the high solids content residual slurry dried solids, the partially carbonized residual slurry dried solids, and the desulfurized gypsum. When the estimated remaining water volume in the mold reaches the preset remaining water volume, the cumulative discharged residual slurry dried solid mass is not greater than the preset solid discharge upper limit, and the slurry mass change rate is not greater than 10% within the corresponding duration, centrifugation is stopped, and a centrifugally formed electric rod is obtained.